(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
Integration of makhana (Euryale ferox Salisb.)-cum-fish culture including sole system as sub-plot on the nutritional quality under wetland ecosystem reveal that seed yield as well as nutritional value of makhana seeds (starch, sugar, protein and minerals) vary significantly by different integrated nutrient management (INM) packages applied on the crop and fishes. The result exhibited highest value (75.04, 2.37, 9.45 and 0.52%) with N4 treatment (plants and fishes both received a well-balanced organic and inorganic sources of plant nutrients along with fish-feed including zinc spray). The combined effect of different farming system and INM on the nutritional status of makhana seeds was not significant. These important food ingredients as fresh as well as its different value-added products have great importance for small and cottage industries, particularly poor and marginal section of rural people as well. DOI: http://dx.doi.org/10.3329/bjsir.v48i4.11501 Bangladesh J. Sci. Ind. Res. 48(4), 281-286, 2013